Next Generation Intelligent Environments Ambient Adaptive Systems - Ultes, Stefan; Nothdurft, Florian; Heinroth, Tobias; Minker, Wolfgang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers key topics in the field of intelligent ambient adaptive systems. It focuses on the results worked out within the framework of the ATRACO (Adaptive and TRusted Ambient eCOlogies) project. The theoretical background, the developed prototypes, and the evaluated results form a fertile ground useful for the broad intelligent environments scientific community as well as for industrial interest groups. The new edition provides: Chapter authors comment on their work on ATRACO with final remarks as viewed in retrospective Each chapter has been updated with follow-up work emerging from ATRACO An extensive introduction to state-of-the-art statistical dialog management for intelligent environments Approaches are introduced on how Trust is reflected during the dialog with the system.
A Middleware Architecture for Ambient Adaptive Systems -- Adaptive Networking -- Ontology-based knowledge management in NGAIEs -- Privacy & Trust in Ambient Intelligent Environments -- Novel Approaches to Artefact Adaptation in Ambient Intelligent Environments -- User Interaction Adaptation within Ambient Environments -- User-centered Spoken Dialogue Management -- Artificial Intelligence Planning for Ambient Environments -- From scenarios to "free-play": Evaluating the user's experience of ambient technologies in the home.
Keywords: Signal processing; User interfaces (Computer systems).; Human-computer interaction; Telecommunication; Signal, Speech and Image Processing; User Interfaces and Human Computer Interaction; Communications Engineering, Networks